Agitating tests of fluid soil admixed with foam in the chamber of EPB shield - Atsushi KAGAWA; Yoshihide SUWA (Nihon Kikai Gakkai ronbunshu, 2022)
The visualization system of soil fluidity in the chamber of EPB (Earth Pressure Balanced) shield has been developed to maintain appropriate fluidity of the excavated soil in real time during the shield advance under the tunnel construction. For further improvement of the visualization system, agitation tests of fluid soil admixed with foam have been carried out to study the relationship between number of rotations and agitating torque of the fluid soil. It is confirmed by the tests that the agitating torque of the fluid sand admixed with the foam reduces with increasing the number of rotations in the range of small number of rotations, and the agitating torque slightly increases in the range of large number of rotations. The phenomena appeared strongly as the volume percentage of foam addition decreased. On the other hand, in case of small weight percentage of fine friction in the fluid soil, the agitating torque reduced with increasing the number of rotations, the torque, however, increased with increasing the number of rotations as the percentage of fine friction increased. It is considered that the relationship between number of rotations and agitating torque of the fluid soil are affected by the friction of sand particles and fluidization due to foam addition and fine fraction in the fluid soil.